How does green credit affect industrial green transformation? Mechanism discussion and empirical test - Xiaowei Song; Lulu Zhang; Siyu Ren (Heliyon, 2024)
Sustainable development has become a strategic consensus in response to the global environmental problems. Green credit is a major policy innovation that promotes the transformation of economic development mode and industrial green transformation (IGT). Using provincial panel data from 2005 to 2020, we investigate the effect of green credit on IGT using a systematic GMM model, a dynamic threshold model, as well as the possible nonlinear relationship. Benchmark regression results show that green credit can encourage industrial green transformation. In addition, there is a single green credit threshold with a value of 0.2612. The trend is “negative to positive”. According to the moderating effect results, environmental regulation moderates in a negative manner. As environmental regulations become more stringent, the contribution of green credit to IGT will diminish. The intermediary mechanism test demonstrates that green technology innovation and marketization level play a partial intermediary role. Heterogeneity testing confirms that the function of green credit in promoting industrial green transformation is more significant in regions with a higher level of green finance development and a lower degree of government intervention. Therefore, the government should encourage financial institutions to provide green credit products and services to meet the financing needs of different green projects, thereby facilitating the industrial green transformation.